Effect of Different Processing Treatments on the Chemical and Sensory Characteristics of Camel Meat Sausage - Yagoub, Yagoub Magboul (Gezira Journal of Agricultural Science; Vol 23 No 1 (2025), 2026)
This study was conducted to evaluate the effect of different processing treatments on the chemical composition and sensory characteristics of camel meat sausage. Three sausage treatments were prepared: control sausage (A), vinegar-treated sausage (B), and finely blended sausage (C). Camel meat samples were processed using standard sausage manufacturing procedures with natural sheep casings and different additives, including spices, fat, filler materials, and binding agents. Chemical analyses were carried out to determine moisture, protein, fat, ash content, and pH values according to AOAC (1984) methods. Sensory evaluation was also performed to assess color, tenderness, juiciness, and flavor of the sausage samples. The results showed significant differences (P < 0.01) among treatments in moisture, protein, ash, and pH values, whereas no significant differences were observed in fat content. The vinegar treatment increased sample acidity, while fine blending reduced moisture and protein contents. Sensory evaluation revealed no significant differences among the three treatments in color, tenderness, juiciness, or flavor.  The study concluded that processing treatments had noticeable effects on the chemical composition of camel meat sausage, whereas sensory properties remained generally acceptable among all treatments.